Management of isolated distal end of radius fracture in pediatric age group: An observational study - Phadke, Vishwas Sharad; Allamwar, Ajaykumar R; Antrolikar, Vaibhav V (Asian Journal of Medical Sciences, 2021)
Background: Fractures of the distal radius are one of the common fractures for which pediatric orthopedic consultations are sought. The usual mechanism of injury is fall on outstretched hand seen following a road traffic accident or fall. Most of these fractures are treated either conservatively or by closed reduction and immobilization in cast. In some cases, internal fixation by K-wiring may be required. We conducted this study to analyzed outcome of distal end radius fracture in pediatric age group who were treated by immobilization alone, by closed reduction and immobilization and closed reduction with internal fixation by K-Wire and immobilization in cast. Aims and Objectives: 1. To analyze outcome of distal end radius fracture in pediatric age group. 2. To study complications in children presenting with distal end radius fracture. Materials and Methods: This was an observational study conducted in the department of orthopedics of a tertiary care medical college. 60 pediatric patients with distal radius fractures and treated either by conservative management or by surgical intervention were included in this study on the basis of a predefined inclusion and exclusion criteria. Gender distribution, mean age and mechanism of injury in the affected cases were analyzed. Patients were treated either by immobilization alone, by closed reduction and immobilization and closed reduction with internal fixation by K-Wire and immobilization in cast. Patients were followed up for 8 weeks. Complications and time for complete union was assessed during follow up visits. Functional outcome was assessed by QuickDash Score. Results: Out of these 60 patients there were 52 (86.66%) males and 8 (13.33%) females with a male to female ratio of 1:0.15. The mean age of affected cases in Boys and Girls was found to be 13.09 +/- 2.93 years and 12.5+/- 3.64 years respectively. Dominant hand was involved in 41 (68.33 %) whereas non-dominant hand was involved in remaining 19 (31.66 %) cases. In 16 (26.67%) patients only casting was required whereas closed reduction and casting was done in 25 (41.67%) patients in remaining 19 (31.67%) patients closed reduction and K-Wire fixation was done. 42 (70%) patients had excellent functional outcome whereas 9 (15%) patients had good functional outcome and 9 (15%) patients were found to have satisfactory outcome. 4 (6.66%) patients developed pressure sores, 1 (1.67%) patient had stiffness and there was 1 (1.67%) case of pin site infections. All these complications were successfully managed by conservative means. Conclusion: Fractures of distal end of radius in pediatric age group can be managed successfully either by immobilization alone or by closed reduction and casting. Internal Fixation by K-Wires may be required in some cases.